2020
DOI: 10.1002/pbc.28559
|View full text |Cite
|
Sign up to set email alerts
|

The use of interval‐compressed chemotherapy with the addition of vincristine, irinotecan, and temozolomide for pediatric patients with newly diagnosed desmoplastic small round cell tumor

Abstract: Background Desmoplastic small round cell tumor (DSRCT) is a rare aggressive sarcoma that affects children and young adults, and portends poor outcomes despite intensive multimodal treatment approaches. We report toxicity, response, and outcomes of patients with DSRCT treated with the addition of vincristine, irinotecan, and temozolomide (VIT) to interval‐compressed chemotherapy as per Children's Oncology Group ARST08P1. Methods All newly diagnosed pediatric patients with DSRCT treated at Dana‐Farber Cancer Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…The proposed treatment strategy provides classic intensive ifosfamide-based regimens (which also use adriamycin and etoposide) with the addition of irinotecan given at a short interval between chemotherapy administrations. The use of the IrIVA regimen may achieve the goal to include a further potentially effective drug such as irinotecan, 13,18 but also to increase the dose-density of the treatment. 13 If in the first part of the treatment the proposed strategy follows the concept of higher dose intensity, in the second part we introduce the concept of a maintenance therapy similarly to a metronomic chemotherapy, which implies regular, frequent administration of low doses of drug with the aim to achieve an antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed treatment strategy provides classic intensive ifosfamide-based regimens (which also use adriamycin and etoposide) with the addition of irinotecan given at a short interval between chemotherapy administrations. The use of the IrIVA regimen may achieve the goal to include a further potentially effective drug such as irinotecan, 13,18 but also to increase the dose-density of the treatment. 13 If in the first part of the treatment the proposed strategy follows the concept of higher dose intensity, in the second part we introduce the concept of a maintenance therapy similarly to a metronomic chemotherapy, which implies regular, frequent administration of low doses of drug with the aim to achieve an antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…An example might be to increase the chemotherapy intensity by administering it with a shorter interval than the usual 3-week time. 13 Following this concept, we explored an intensive multiagent chemotherapy including most drugs generally adopted in pediatric sarcomas treatment plus a new chemotherapy regimen that uses irinotecan, ifosfamide, vincristine, and actinomycin-D (IrIVA), with irinotecan being given for 5 consecutive days during the second week of the classic ifosfamide, vincristine, and actinomycin-D (IVA) cycle. The IrIVA regimen was originally conceived by and recently investigated in an Italian study on metastatic rhabdomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Scheer et al [ 52 ] found that patients treated with the VAIA regimen (ifosfamide, vincristine, doxorubicin, actinomycin D) presented longer event-free survival (29.4 months) compared to other protocols, including the P6 protocol. The interval-compressed regimen of vincristine, irinotecan, temozolamide (VIT) was evaluated in 6 pediatric patients and showed a tolerable profile with an objective response rate of 50% to the first 2 cycles of VIT [ 53 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This introduces the potential for misdiagnosis of other round cell sarcomas as Ewing sarcoma in the setting of a positive EWSR1 translocation when an alternative diagnosis (eg, desmoplastic small round cell tumor) would have been rendered if the fusion partner (eg, WT1) was identified by the testing strategy. In some cases (eg, desmoplastic small round cell tumor), the treatment paradigm would differ by molecular findings, 15 while in other cases (eg, an emerging group of round cell sarcoma with EWSR1-non ETS fusions) the optimal therapy may still be unknown. 12,13 It will be of interest to determine if patterns of testing evolve as NGS approaches that provide information on both fusion partners become more widely available.…”
Section: Per Patient Analysismentioning
confidence: 99%